Delmar's nursing fundamentals critical thinking CD-ROM (Albany, NY : Delmar Thomson Learning, 2002)
Containing a content-rich library of twenty nursing case studies that emphasize clinical judgement and a dynamic review of anatomy & physiology.
System requirements : 2x CD-ROM drive ; 100Mhz Pentium w/24 MB of RAM,32 MB pr more of RAM, Sound card and speakers, Windows 95, SVCGA with 24-bit display, 8 MB free disk space.
Keywords: Nursing process; Nursing Care; Thinking; Decision making